Characterization of Co-Stimulatory Ligand CD80/86 and Its Effect as a Molecular Adjuvant on DNA Vaccine Against Vibrio anguillarum in Flounder (Paralichthys olivaceus) - Liu, Wenjing; Xing, Jing; Tang, Xiaoqian; Sheng, Xiuzhen; Chi, Heng; Zhan, Wenbin (Frontiers in Immunology, 2022)
The CD80/86 molecule is one of the important co-stimulatory ligands and involves antigen-specific immune responses by ligating with CD28 then delivering the required second signal to T cell activation. In this study, CD80/86 homolog was identified and its expression characteristics were studied in flounder (Paralichthys olivaceus). The open reading frame (ORF) of CD80/86 is 906 bp, encoding 301 aa, and the extracellular amino acid sequence encoded two IgV and IgC-like structural domains; fCD80/86 is highly expressed in head kidney, peripheral blood leukocytes (PBLs) and spleen, and relatively high expression in muscle. Antibodies specific for CD80/86 were produced and CD80/86 was co-localized with MHCII, CD40 and CD83 on lymphocytes and not IgM+, CD3+ or CD4+ lymphocytes. The cloned CD80/86 in flounder shares conserved structural features with its mammalian counterparts and is mainly distributed on the antigen-presenting cells. Based on these data, CD80/86 as an adjuvant to enhanced the immune response of DNA vaccine was investigated. A biscistronic DNA vaccine expressing both CD80/86 and outer membrane protein (OmpK) of Vibrio anguillarum (p-OmpK-CD80/86) was successfully constructed. After immunization, p-OmpK-CD80/86 could induce the up-regulation of the proportion of IgM+ and CD4+ cells in flounder, compared to p-OmpK or p-CD80/86 immunized group; CD28 genes were significantly induced in p-CD80/86 and p-OmpK-CD80/86 groups. Compared to the group of p-OmpK, the higher expression of CD83, MHCI, CD4, CD8 and IL-2 were detected at the injection site. The relative percent survival (RPS) produced by p-OmpK-CD80/86 is 66.11% following V. anguillarum challenge, while the RPS of p-OmpK or p-CD80/86 is 46.30% and 5.56%, respectively. The results revealed that CD80/86 mainly on the APCs, and could aid to elicit humoral immune responses in teleost through the CD80/86-CD28 signaling pathway involving CD4+ lymphocytes.